Challenges in the Management of Recurrent Aphthous Stomatitis: A Call for Action on Drug Availability and Alternative Therapies - Muhammad Sadat; Ramzan, Muhammad Haris (Pakistan Armed Forces Medical Journal, 2025)
Dear Editor, Recurrent Aphthous Stomatitis (RAS) is one of the most common clinical oral mucosal disease having prevalence ranging from 5% to 25% in general population,1 with peak incidence in the second decade of life, and about 50%-60% in the professional population.2 The exact etiology of the RAS is unclear; however, it is thought that several factors such as local trauma, psychological stress, immune system imbalance and genetic predisposition factors may contribute to its development. Recurrent Apthous Stomatitis (RAS) episodes can significantly impair patients’ quality of life.3–5 Despite of its high prevalence,5 RAS remains underreported and often overlooked public health issue, largely due to limited number of research studies. One of the major challenges in the effective management of RAS is the unavailability of effective treatment options in the local market. Traditionally, topical corticosteroids, including Triamcinolone Acetonide (oral-base ointment), have long been recognized for their effectiveness in managing RAS manifestations by immune modulatory and anti- inflammatory actions.6 In recent times, this formulation has become unavailable in the local market, creating a challenge in the management of RAS for the clinicians and the patients. Although some alternate topical treatments are also available, which includes Lidocaine-CPC combination (pain relief and antiseptic), antifungals (like Miconazole, Nystatin), and antivirals (e.g Acyclovir), however these treatment options do not offer the .